2021
DOI: 10.48550/arxiv.2101.04296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fits and Starts: Enterprise Use of AutoML and the Role of Humans in the Loop

Abstract: AutoML systems can speed up routine data science work and make machine learning available to those without expertise in statistics and computer science. These systems have gained traction in enterprise settings where pools of skilled data workers are limited. In this study, we conduct interviews with 29 individuals from organizations of different sizes to characterize how they currently use, or intend to use, AutoML systems in their data science work. Our investigation also captures how data visualization is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We continued to the uploaded visualization examples and asked the participant to walk us through the authoring process. To help the participants delineate the authoring process and reflect on their choices, we selected questions from our interview guide, focusing on various topics based on prior literature and user studies on processes involving visualization authoring, user roles in work processes, and criteria for evaluating tools [3,4,16,23]. These questions included: We piloted the interviews with two participants to test the interview guide and pair-interview dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…We continued to the uploaded visualization examples and asked the participant to walk us through the authoring process. To help the participants delineate the authoring process and reflect on their choices, we selected questions from our interview guide, focusing on various topics based on prior literature and user studies on processes involving visualization authoring, user roles in work processes, and criteria for evaluating tools [3,4,16,23]. These questions included: We piloted the interviews with two participants to test the interview guide and pair-interview dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…including wrapping, can answer such questions even in much more detail. In this sense, Naive AutoML presents itself as more amenable to the growing demand for meaningful interaction between the tool and the human [31,4,5,30] compared to the currently adopted black-box approaches.…”
Section: A Prototype For a Stage Schemementioning
confidence: 99%
“…At this point, we shall stress that the main goal of this paper is not to present yet another tool for AutoML but to propose a different view on how automated machine learning could be done. Recent work has revealed that several aspects of the black-box character of current systems impede experts from trusting their output, and that there is a need for more interaction between the tool and the expert [31,4,5,30]. Since Naive AutoML effectively imitates a data scientist, it makes an important step into this direction by adopting an optimization process that is much more comprehensive for an expert who interacts with it.…”
Section: Introductionmentioning
confidence: 99%
“…While these results might suggest Quasi-Naive AutoML as a meaningful baseline over which one should be able to substantially improve, we see the actual role of Quasi-Naive AutoML as the door opener for sequential optimization of pipelines. The currently applied black-box optimizers come with a series of problems discussed in recent literature such as lack of interpretability and flexibility [5,4]. The naive approaches follow a sequential optimization approach, optimizing one component after the other.…”
Section: Introductionmentioning
confidence: 99%